Melek Industri Belum Tentu Melek Finansial : Analisis Kualitatif Literasi Keuangan Dan Perilaku Pengambilan Keputusan Ekonomi Karyawan Pada Sebuah Perusahaan Asuransi Dalam Group Ekosistem Keuangan Terintegrasi - Indri Anggraeni Wulansari; Sitti Rakhman (Jurnal Deliberatif, 2026)
Abstract Financial literacy is a key determinant of individuals' economic behavior and decision-making quality. The 2024 National Survey on Financial Literacy and Inclusion (SNLIK) reports a national financial literacy index of only 65.43%, lower than the 75.02% financial inclusion index, indicating that access to financial products has outpaced understanding of them. This warrants investigation among financial industry employees, typically assumed to be financially literate. This paper examines the financial literacy of employees at an insurance company within an integrated financial ecosystem group, and its correlation with economic behavior and decision-making. Using a qualitative descriptive case study approach, data were gathered through in-depth interviews with seven informants across different positions, observation, and document analysis, then analyzed thematically (Miles & Huberman), with validity assessed via source and technique triangulation. Findings show generally good financial literacy, particularly regarding risk concepts, but weaknesses in investment diversification. All informants agreed that working in finance does not equate to being financially literate; knowledge does not always translate into disciplined behavior. The group's integrated financial ecosystem proved a double-edged sword, improving financial behavior overall while fostering consumptive tendencies among junior employees. The study proposes a sustainable, practical internal financial education program incorporating planning simulations as an HR development strategy. Keywords: financial literacy, financial behavior, economic decision-making, human resource management, insurance